Influencia del clima social familiar en el rendimiento académico de los alumnos del 3°, 4° y 5° grado del nivel secundario de la i.e. divino maestro n° 80016. paragueda, otuzco, la libertad en el año 2014. - Castro Minchola, Luzmila Rocio (2015)
This research was conducted with the objective to identify the influence of the Social Climate Family in the academic performance of students in 3rd, 4th and 5th grade of the secondary level of the E. I. "Divine Master N°. 80016 ". It is considered that the participation of parents in the educational process is one of the primary factors that can contribute to the process of student learning and development of values in the integral formation of the student. In the research involved 45 students. For the collection of information are applied to the family of social climate (FES) of Moos, which is divided into three dimensions; relations, development and stability, the same that are a measure perceptual, personal and individual of the family environment. They also used the consolidated records of student assessment. The results indicate a significant relationship between one of the aspects of the family atmosphere with the academic performance of students. This research concludes that students perceived a social climate suitable family relation in the dimension, which tells us that there is communication, free expression and the ability to resolve conflicts; a social climate inadequate family in the development dimension, due to the fact that parents do not provide guidance to their children to have autonomy, nor promote activities social, recreational, cultural and intellectual to enable them to develop their skills; a social climate suitable family in the dimension stability which implies that there is a good family functioning in terms of control and organization. The academic performance of students is to regulate, because conflicting family situations, education permissive parents and personal factors that affect their school performance, such as lack of concentration. There is a relationship between the social climate suitable family and the academic performance of students, the existence of a positive family environment, will ensure that students are motivated to study.